Study of local and andon fishermen's attitudes towards the minister of marine affairs and fisheries regulation No. 36 of 2014 in Balikpapan City, East Kalimantan - Zaky Abdul Fadhil; Erwiantono Erwiantono; Oon Darmansyah (Faculty of Fisheries and Marine Science, Mulawarman University, 2024)
The purpose of this research is to study the attitude of local and Andon fishermen towards the Regulation of the Minister of Marine Affairs and Fisheries No. 36 of 2014 in Balikpapan City, East Kalimantan. The sample method used is purposive sampling method with the number of respondents taken as many as 30 people consisting of (25 people for local fishermen of Balikpapan City with profession as boat captain and crew, and 5 people for andon fishermen with profession as boat captain and crew).